Some Notes on the Energy Metabolism of Gadus callarias and Gadus virens in Relation to Body Size - Mahhargo Suprapto (Journal of Mathematical and Fundamental Sciences, 1972)
The present work of oxygen consumption in Gadus callarias and Gadus virens shows that there is a connection between the body size and the acclimation time required for reaching a "normal" level of metabolism after being transferred to another aquarium (fig. : 1, 2, 3 & 4). The oxygen consumption under standard condition shows that there is a clear linear regression between the two variable used. However, the significant coefficient does not exclude the possibility of a difference in oxygen consumption in relation to the weight between small fish and bigger ones.